Technical efficiency of certified maize seed in Palpa district, Nepal: A stochastic frontier production approach - Bajracharya, Mahima; Sapkota, Mahesh (Journal of Maize Research and Development, 2018)
The cereal crop, maize is regarded as staple food mainly in hill areas of Nepal. Seed is one of the vital input which determines the production and yield of any crop. Farmers are found using the required inputs in haphazard way which had increased the cost of production and inefficiency of resources used. The study on seed sector is limited. For such a backdrop, this study was aimed to assess the level of technical efficiency (TE) of certified maize seed production. The total of 164 certified seed producer were interviewed in June, 2016 using simple random sampling technique in Palpa district of Nepal. The result revealed that increase in amount of seed and labor by one percent would increase the yield of certified maize seed by 0.29 and 0.34 percent respectively. The TE was estimated using stochastic production frontier model in Stata software. The average TE was found 70 percent which revealed the scope of increasing TE by 30 percent using the existing available resources. There were about 29 percent farmers who had TE of ≥0.7-0.8 followed by 27.44 percent at ≥0.8-0.9. Government and other stakeholders should prioritize to provide technical knowledge via training and increase the visit of extension worker to increase TE of certified maize seed producer in the district.